2006
DOI: 10.1097/01.psy.0000242124.21796.f8
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits, Coping Style, and Perceived Threat as Predictors of Posttraumatic Stress Disorder After Exposure to a Terrorist Attack: A Prospective Study

Abstract: The findings indicate that premorbid personality characteristics, as well as subjective and objective factors related to the traumatic exposure, increased the risk for the development of PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 9 publications
9
65
0
2
Order By: Relevance
“…This view is supported by prospective studies that have found personality traits such neuroticism and HA to be predictive of future mood-and anxiety symptoms or disorders (Cloninger et al, 2006;Elovainio et al, 2004;Gil and Caspi, 2006;Kendler et al, 2006). Even tough association between human personality and psychiatric illnesses is likely to be more complex, there is heuristic value in considering certain personality traits as vulnerability factors as it provides a unique way to study the neurobiology of risk for psychiatric disorders in healthy population.…”
Section: Introductionmentioning
confidence: 90%
“…This view is supported by prospective studies that have found personality traits such neuroticism and HA to be predictive of future mood-and anxiety symptoms or disorders (Cloninger et al, 2006;Elovainio et al, 2004;Gil and Caspi, 2006;Kendler et al, 2006). Even tough association between human personality and psychiatric illnesses is likely to be more complex, there is heuristic value in considering certain personality traits as vulnerability factors as it provides a unique way to study the neurobiology of risk for psychiatric disorders in healthy population.…”
Section: Introductionmentioning
confidence: 90%
“…Over time, these responses diminish for most survivors (Kessler et al 1995;Rothbaum et al 1992); however, some will go on to develop chronic symptoms of reexperiencing, avoidance, emotional numbing, and hyperarousal, indicative of a posttraumatic stress disorder diagnosis (PTSD; American Psychiatric Association (APA) 1994; Gil and Caspi 2006;Kessler et al 1995). As such, trauma exposure alone is not sufficient for explaining the development of PTSD, and other factors are thought to play an important role in increasing risk for PTSD following exposure to a traumatic event (Miller 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pre-morbid distress proneness prior to onset of AD was found to correlate with the extent of episodic memory impairment once the disease was established (Wilson et al, 2004). Moreover, in AD patients, a greater frequency and impact of stressful life events throughout life was found associated with an increase in some personality traits, such as passivity and avoidance (Clement et al, 2003), suggestive of a deficit in the ability to cope with stress (Davey et al, 1995;Gil and Caspi, 2006). Thus, all together, these data suggest that stressful events can play a critical role in the early development of cognitive symptoms in AD in individuals vulnerable to stress.…”
Section: Clinical Studiesmentioning
confidence: 82%